Unusual presentation of Ramsay‐Hunt Syndrome in kidney transplant patient - Via Reque Cortes, Daniela Del Pilar; Paes Menezes Filho, Marcelo; Braga Barbosa, Géssica Sabrine; Didier M. Ferreira, Tomás; Reusing, José Otto; David Neto, Elias (Transplant infectious disease, 2021)
Herpes Zoster (HZ) is caused by reactivation of latent varicella zoster virus (VZV) in craniospinal sensory neurons and is characterized by a painful erythematous rash in the affected dermatome. Although kidney transplant recipients who are chronically maintained on immunosuppressive regimens are considered at risk, there are only a few cases described. We report a well‐documented case of a 50‐year‐old male kidney transplant recipient who presented Ramsay‐Hunt syndrome with atypical neurological finds.